2015
DOI: 10.3109/01913123.2014.991884
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α and VEGF: Immunohistochemical Profile and Possible Function in Human Aortic Valve Stenosis

Abstract: Calcific aortic stenosis (CAS) is the most common valvular disease in Western countries. Histological findings in patients with CAS extremely resemble those of atherosclerosis and include accumulation and modification of lipoproteins, inflammation, extracellular matrix remodeling, and calcification. Angiogenesis is another prominent feature of CAS; however, there is only a limited amount of data available regarding the mechanisms behind the pathological neovascularization of a structure that is originally avas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…HIF-1a, a marker frequently associated with angiogenesis, has recently been identified histologically in CAVD [21,22]. The impact of hypoxia on HIF-1a activation rsif.royalsocietypublishing.org J. R. Soc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF-1a, a marker frequently associated with angiogenesis, has recently been identified histologically in CAVD [21,22]. The impact of hypoxia on HIF-1a activation rsif.royalsocietypublishing.org J. R. Soc.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that hypoxia inducible factor 1-alpha (HIF-1a) is present in calcific nodules in CAVD [21,22]. Valve architecture, which greatly affects oxygen diffusion and transport, is different between the aortic and mitral valves.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinical data also implicate close relationship between HIF and vascular calcification. Both HIF-1α and HIF-2α activation have been localized in calcified aorta valve [129,130]. Li G et al also showed that elevated serum HIF-1α may be involved in coronary artery calcification by analysis of the computed tomography scanning data of 405 patients with type 2 diabetes mellitus [131].…”
Section: Hif In Ckd-associated Syndromesmentioning
confidence: 99%
“…Vegfa and Icam1 transcription: two signaling markers previously described in CAVD. 55,56 Importantly, STAT3β not only opposes STAT3α activity, thereby decreasing RUNX2 transcription, but also directly binds to RUNX2, preventing its activity as a transcription factor. 57 These phenomena translated to human AVs: STAT3β decreases in calcified regions of diseased AVs and negatively correlates with RUNX2 expression.…”
Section: Discussionmentioning
confidence: 99%